2015
DOI: 10.1007/s10068-015-0130-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of freeze-dried Tibetan kefir co-culture as a starter for production of Bod ljong cheese

Abstract: The physico-chemical profile, proteolysis, flavor, and microbiological changes were investigated, and a sensory evaluation was performed for Bod ljong cheese prepared using a freeze-dried Tibetan kefir co-culture during ripening. The proteolysis level was high, the pH 4.6-soluble nitrogen, 12% trichloroacetic acid-soluble nitrogen, water soluble nitrogen, and total free amino acid contents increased, and the protein content decreased during ripening. The effect of the starter culture on production of aroma-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Determination of volatile flavour compounds. The volatile flavour compounds were determined by the methods of Nambou et al (2014) and Mei et al (2015). Five grams of mulberry juice-whey beverage (MJWB) samples were used.…”
Section: Methodsmentioning
confidence: 99%
“…Determination of volatile flavour compounds. The volatile flavour compounds were determined by the methods of Nambou et al (2014) and Mei et al (2015). Five grams of mulberry juice-whey beverage (MJWB) samples were used.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that TKG can be used for other dairy products manufacturing, for example, Camembert type cheese [19,20], and traditional Chinese Bod ljong cheese [21]. The fermenting activity of TKG has been shown not only for milk, but also for a mixture of mulberry juice and whey [22].…”
Section: Introductionmentioning
confidence: 99%
“…LAB may derive from kefir and, together with some yeasts, would dominate the kefir metabolism product. Previous studies used kefir as the source of LAB for cheese production and reported that kefir would affect the physical properties of cheese during ripening Studies on cheese characteristics using kefir as a starter have been conducted, namely wet/liquid kefir for white pickled cheese (Goncu and Alpkent, 2005;et al, 2006), freezedried kefir for feta cheese for people with high blood pressure (Kourkoutas et al, 2006) and freeze-dried Tibetan kefir for Bod Ijong cheese (Mei et al, 2015). Based on these studies, it is evident that kefir as cheese starter could produce cheese with marketable properties (Kourkoutas et al, 2006;Mei et al, 2015), including the more preferable pH (acidity), appearance, structure, and aroma compared to cheese made of commercial and yoghurt starters (Goncu and Alpkent, 2005).…”
Section: Introductionmentioning
confidence: 99%